2022
DOI: 10.7759/cureus.22862
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Postoperative Outcomes of Clavicle Midshaft Fracture Treated by Nailing vs. Plating

Abstract: BackgroundA midshaft clavicle fracture is a prevalent form of injury of the upper extremity that affects one's quality of life. Several treatment modalities facilitate fixation of the displaced midshaft clavicle to decrease nonunion and malunion of the clavicle fracture. Still, numerous factors influence choosing an optimal surgical intervention. Thus, this study investigates the functional outcome of two standard fixation techniques, titanium elastic nails (TENs) and locking plates, as a prospective comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…On the basis of these findings, the authors concluded that both plating as well as nailing provided good functional outcome and permitted early return to occupational activities. Yadav et al (2022) [23] "performed closed/open reduction and internal fixation in 62 patients (40 male and 22 female) with TENs and locking plates, respectively, which were followed up at regular intervals following the surgery (at two, six, 12, 24, and 48 weeks). The surgical outcome was assessed both from functional and radiological standpoints.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these findings, the authors concluded that both plating as well as nailing provided good functional outcome and permitted early return to occupational activities. Yadav et al (2022) [23] "performed closed/open reduction and internal fixation in 62 patients (40 male and 22 female) with TENs and locking plates, respectively, which were followed up at regular intervals following the surgery (at two, six, 12, 24, and 48 weeks). The surgical outcome was assessed both from functional and radiological standpoints.…”
Section: Introductionmentioning
confidence: 99%